Pengembangan E-Modul pada Materi Koloid untuk Meningkatkan Kemampuan Berpikir Kreatif Peserta Didik - Wahyuliani, Dwi; Danial, Muhammad; Sanusi, Wahidah (Chemistry Education Review (CER), 2022)
This study is a research and development that aims to develop electronic modules using Flip PDF Professional on colloid material to improve students' creative thinking skills that are valid, practical, and effective to be used. The development model used refers to the ADDIE development model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. The electronic module developed using Flip PDF Professional software had been validated by material expert and media expert and had gone through a trial phase to produce a valid, practical, and effective Colloid Chemistry electronic module. The Colloid Chemistry E-module product made with Flip PDF Professional is attractively designed because it contains colloid learning video and animation, and is practical in its use because students can easily access it on their respective androids without having to use additional applications. The subjects in this study were students of grade XI MIPA 3 at UPT SMAN 2 Parepare City. The results show that the Colloid Chemistry electronic module developed using Flip PDF Professional software obtained 88.5% validity by material expert and 86.12% validity percentage by media expert, so the validator criteria for the electronic module obtained as valid. The Colloid Chemistry electronic module developed using Flip PDF Professional software is stated to be practical because the practicality test obtained an average of 3.625 with practical criteria from the results of teacher’s responses and an average of 3.772 from students’ responses with practical criteria. The electronic product of the Colloidal Chemistry module also meets the effectiveness criteria based on the test result of students' creative thinking skills after using the developed colloid chemistry module, where students' creative thinking skills are dominated at level 3, namely creative.